Mediating role of readiness for change in the relationship between principal instructional leadership and commitment to change - Abdul Aziz, Nor Azni; Asimiran, Soaib; Hassan, Aminuddin (Inderscience Publishers, 2022)
The research's goals are to assess the principal instructional leadership's impact on teachers' commitment (normative, continuance, and affective) for change in adopting School-Based Assessment (SBA). Furthermore, this research aims to identify the function of a mediator, notably in teachers' readiness for change in the application of SBA. The research's findings discovered that the developed study model fits with the values of Goodness of Fit Index (GFI) = 0.902; Comparative Fit Index (CFI) = 0.934; Tucker-Lew Index (TLI) = 0.925; and Root Mean Square of Error Approximation (RMSEA) = 0.055.The results showed a significant impact between principal instructional leadership with teachers' commitment (normative, continuance and affective) to change and teachers' readiness for change. According to the findings of the mediator assessment, teachers' readiness to change was established as a partial mediator in the relationship between principal instructional leadership and teachers' commitment (normative, continuance and affective) to change in the deployment of the SBA methodology. To ensure that changes in education such as SBA will successfully achieve the educational targets, principals need to act as instructional leaders to enhance teachers' readiness and commitment in implementing any educational changes.